The Applicability of Leasing Contracts in Islamic Law Perspective to Enhance the Economic Growth in Indonesia - Ismail Jalili (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
The lease finance contract plays a significant role in contemporary financial operations in Indonesia. However, the lease contract must adhere to Islamic law and government regulations in order to promote the reliability of leasing within society and among business participants. The purpose of this study was to analyze the compliance of leasing practices in Indonesia to Islamic law and regulatory standards, as well as to evaluate the level of compliance and protection provided by legal provisions in leasing contracts for small and medium-sized businesses operating in the home industry sector in Indonesia. This study employs a qualitative analytical method based on the application of a statutory and conceptual approach to data description and analysis. The results show that the leasing activities carried out by business entities in Indonesia are conducted in compliance with the principles of Islamic law and the regulations set by the government. Leasing has demonstrated its significant role in fostering economic expansion and augmenting state revenue. Nevertheless, it is anticipated that the government will assume a more proactive role in enhancing consumer protection and ensuring efficient oversight, so ensuring that leasing practices adhere to current legal regulations